From Supplier Excellence to Procurement Success: The Mediating Role of Competitive Advantage in Driving Procurement Performance - Hidayat, Fadhillah Syarief; Pragiwaksana, Angilbert Enggar; Xuan, Nie; Sudrajat, Darjat; Maharani, Anita (Jurnal Locus Penelitian dan Pengabdian, 2026)
In an increasingly competitive and globalized business environment, procurement has evolved from a transactional function to a strategic driver of organizational efficiency and competitive advantage. The quality and service performance of suppliers are critical, yet their pathway to influencing overall procurement success requires further empirical exploration. This research aims to analyze the influence of supplier quality and supplier services on procurement competitive advantages and their impact on procurement performance. In an increasingly competitive business environment, procurement functions play a strategic role in supporting operational efficiency and a company’s competitive edge. This research employs a quantitative approach, collecting data through surveys of procurement managers across various industry sectors. Structural Equation Modeling (SEM) is used for data analysis. The results indicate that both supplier quality and supplier services have a positive and significant impact on procurement competitive advantages. Furthermore, procurement competitive advantages significantly enhance procurement performance, particularly in terms of cost efficiency, responsiveness, and internal stakeholder satisfaction. These findings highlight the importance of building strategic relationships with high-quality and responsive suppliers to achieve superior procurement performance.